Active Methodologies: As ICT as inclusive tools to teach PLE to the spanish visually impaired - Dos Santos Ribeiro, Lilian (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article proposes the approach of an approach centered on the approach of the approach as ICT tools to facilitate the teaching-learning of PLE to Spanish visually impaired. Given the introductory, panoramic and clearly accessible nature and nature of this work, the reader will be able to have a direct and scientific understanding of the educational world to educate the perfected visual.The work methodology used was quantitative and qualitative supported by relevant bibliography, the work methodology used was researched through interviews with directors, professors, professors and relevant students; surgeries and internships in rehabilitation centers for blind and visually impaired people. After some analyzes and interviews carried out by some results and methodologies after applied to different students in rehabilitation centers and for the last time made the analysis. Some were also used in PLE groups outside of rehabilitation centers.